Integrating Motivational Interviewing in Pain Neuroscience Education for People With Chronic Pain: A Practical Guide for Clinicians. Issue 5 (29th January 2020) - Nijs, Jo; Wijma, Amarins J; Willaert, Ward; Huysmans, Eva; Mintken, Paul; Smeets, Rob; Goossens, Mariëlle; van Wilgen, C Paul; Van Bogaert, Wouter; Louw, Adriaan; Cleland, Josh; Donaldson, Megan
Abstract: Pain neuroscience education (PNE) and motivational interviewing (MI) have been widely implemented and tested in the field of chronic pain management, and both strategies have been shown to be effective in the short term (small effect sizes) for the management of chronic pain. PNE uses contemporary pain science to educate patients about the biopsychosocial nature of the chronicity of their pain experience. The goal of PNE is to optimize patients' pain beliefs/perceptions to facilitate the acquisition of adaptive pain–coping strategies. MI, on the other hand, is a patient-centered communication style for eliciting and enhancing motivation for behavior change by shifting the patient away from a state of indecision or uncertainty. Conceptually, PNE and MI appear to be complementary interventions, with complementary rather than overlapping effects; MI primarily improves cognitive and behavioral awareness and, potentially, adherence to treatment principles, whereas PNE potentially increases pain knowledge/beliefs, awareness, and willingness to explore psychological factors that are potentially associated with pain. Therefore, combining PNE with MI might lead to improved outcomes with larger and longer-lasting effect sizes. The combined use of PNE and MI in patients having chronic pain is introduced here, along with a description of how clinicians might be able to integrate PNE and MI in the treatment of patients experiencing chronic pain. Clinical trials are needed to examine whether combining PNE with MI is superior to PNE or MI alone for improving pain and quality of life in patients having chronic pain.